Pharmacovigilance and Adverse Drug Reaction (ADR): A case study - Dr.Amit Kumar, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2018)
World Health Organization (WHO) and Uppsala Monitoring Centre (UMC) work with and provide technical support to more than 94 countries worldwide. Several disasters led to an awareness that drugs not only can heal but also can harm including sudden death caused by chloroform anaesthesia in 1877 and fatal hepatic necrosis due to arsenicals in 1922. In the United States a tragic mistake in the formulation of a children’s syrup in the late 1930s was the trigger for setting up the product authorization system under the Food and Drug Administration (FDA). The Food and Drug Administration had the authority to review new drugs for safety, by scrutinizing animal studies and small human volunteer trials for any signs of serious hazards. In order to prevent unnecessary suffering by patients and to decrease the financial loss sustained by the patient due to the inappropriate or unsafe use of medicines, it is essential that a monitoring system for the safety of medicines in Country is supported by doctors, pharmacists, nurses and other health professionals in the country. The Drug Regulatory Authority (DRA) and National Pharmacovigilance programme, adverse reactions should be reported on a daily basis. A case study has done on the basis of Adverse Drugs Reaction in Chandigarh. The patient was named Pratigya Choudhary, age four year six months old. Prescription of Amoxicillin and Potassium Clavulanate combination given to patient and found Jaundice after two dosages. The patient was serious to admit in Hospital. The ultimate goal of this activity is to improve the safe and rational use of medicines, thereby improving patient care and public health.